Aspirin use is associated with decreased radiologically-determined thrombus sac volume in abdominal aortic aneurysms. (August 2018) - Balceniuk, Mark D; Trakimas, Lauren E; Aghaie, Claudia; Mix, Doran; Rasheed, Khurram; Ellis, Jennifer; Glocker, Roan; Doyle, Adam; Stoner, Michael C
Introduction: Formation and renewal of intramural thrombus is associated with inflammation, and contributes to the complexity of aneurysm repair. Current cardiovascular pharmacotherapy includes several inflammatory modulators such as aspirin, statins, clopidogrel, and angiotensin-converting enzyme inhibitors. The purpose of our study was to investigate the effect of these inflammatory modulators on radiographically-determined thrombus sac volume. Methods: Pre-operative computed tomography scans were reviewed in patients who underwent elective infrarenal aortic aneurysm repair. Thrombus sac volume was obtained using a Hounsfield unit restricted region growth algorithm. Co-morbid conditions such as diabetes mellitus and post-operative complications were evaluated compared to thrombus sac volume. Receiver–operator characteristic curves were generated for thrombus sac volume and patients on the various cardiovascular pharmacotherapies. Results: A total of 266 patients (mean age = 72.6 ± 0.6 years; mean thrombus sac volume = 58.7 (34.4–89.0) cm 3 ) were identified. Acetylsalicylic acid use was associated with a decreased thrombus sac volume ≤50 cm 3 (AUC = 0.616, p  = 0.013) whereas statins ( p  = 0.26), angiotensin-converting enzyme inhibitors ( p  = 0.46), and clopidogrel ( p  = 0.62) had no correlation to thrombus sac volume. Diabetes mellitus was not associated with thrombus sac volume ( p  = 0.31). Conclusion: Acetylsalicylic acid use is associated with decreased thrombus sac volume in a patient population undergoing elective abdominal aortic aneurysms repair. The effect of acetylsalicylic acid over other anti-inflammatory and anti-platelet agents is possibly attributable to its distinct mechanism of cyclooxygenase-1 inhibition. Diabetes mellitus, a known correlate of aneurysm incidence, is not associated with thrombus burden. The potential to alter aneurysm thrombus volume, thereby affecting aneurysm morphology, may yield a more favorable aneurysmal repair.